Asthma: The importance of dysregulated barrier immunity. (20th November 2013) - Lambrecht, Bart N.; Hammad, Hamida
<x xml:space="preserve">Abstract</x> Chronic asthma is an inflammatory disease of the airway wall that leads to bronchial smooth muscle hyperreactivity and airway obstruction, caused by inflammation, goblet cell metaplasia, and airway wall remodeling. In response to allergen presentation by airway DCs, T‐helper lymphocytes of the adaptive immune system control many aspects of the disease through secretion of IL‐4, IL‐5, IL‐13, IL‐17, and IL‐22, and these are counterbalanced by cytokines produced by Treg cells. Many cells of the innate immune system such as mast cells, basophils, neutrophils, eosinophils, and innate lymphoid cells also play an important role in disease pathogenesis. Barrier epithelial cells are being ever more implicated in disease pathogenesis than previously thought, as these cells have in recent years been shown to sense exposure to allergens via pattern recognition receptors and to activate conventional and inflammatory‐type DCs and other innate immune cells through the secretion of thymic stromal lymphopoietin, granulocyte‐macrophage colony stimulating factor, IL‐1, IL‐33, and IL‐25. Understanding this cytokine crosstalk between barrier epithelial cells, DCs, and immune cells provides important insights into the mechanisms of allergic sensitization and asthma progression as discussed in this review.